Litter size for gilts fed higher levels of folic acid and Riboflavin during gestation - C Zhang; D Li; Jim L Nelssen; Duane L Davis (Kansas Agricultural Experiment Station Research Reports, 1990)
We fed gilts diets containing either additional folic acid throughout gestation (1.5 g/ton, 4.5 lb/gilt daily), additional riboflavin (100 mg/gilt daily) from d 4 to 10 of gestation, both folic acid and riboflavin, or neither supplement All diets provided all KSU recommended allowances for all other nutrients. Neither farrowing rate nor litter size was affected by the treatments.; Swine Day, Manhattan, KS, November 15, 1990
Keywords: Swine day; 1990; Kansas Agricultural Experiment Station contribution; no. 91-189-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 610; Swine; VitB; Riboflavin; Gestation; Litter; Sow; Performance